Dinasti Saljuk dan pertumbuhan ekonomi di Asia Barat: Keberhasilan dalam membangun perekonomian berkelanjutan pada abad pertengahan - Putra, Alvino Pramana (Maliki Interdisciplinary Journal, 2024)
The purpose of this article is to reveal political successes and failures during the Umayyad era. The research method in this article is qualitative, while the research method in this article is an explanation of qualitative analysis by examining various sources related to policies during the Umayyad era. The results or conclusions of this research recognize that leadership in history often has a dramatic impact on societal development. There are two important people in the history of the Umayyad Caliphate, namely Caliph Umar bin Abdul Aziz and Caliph Umar bin Sayyar, both of whom provide different descriptions of the success and failure of government in different situations. This article will discuss and analyze what caused the success of Caliph Umar bin Abdul Aziz and the failure of Caliph Umar bin Sayyar during the reign of Caliph Marwan II.